Prevalence and Characteristics of Asthma-Chronic Obstructive Pulmonary Disease Overlap in Routine Primary Care Practices. - Krishnan, Jerry A.; Nibber, Anjan; Chisholm, Alison; Price, David; Bateman, Eric D.; Bjermer, Leif; van Boven, Job F. M.; Brusselle, Guy; Costello, Richard W.; Dandurand, Ronald J.; Diamant, Zuzana; Van Ganse, Eric; et al. (Annals of the American Thoracic Society, 2019)
Rationale: Adults may exhibit characteristics of both asthma and chronic obstructive pulmonary disease (COPD), a situation recently described as asthma-COPD overlap (ACO). There is a paucity of information about ACO in primary care.Objectives: To estimate the prevalence and describe characteristics of individuals with ACO in primary care practices among patients currently diagnosed with asthma, COPD, or both; and to compare the prevalence and characteristics of ACO among the three source populations.Methods: The Respiratory Effectiveness Group conducted a cross-sectional study of individuals ≥40 years old and with ≥2 outpatient primary care visits over a 2-year period in the UK Optimum Patient Care Research Database. Patients were classified into one of three source populations based on diagnostic codes: 1) COPD only, 2) both asthma and COPD, or 3) asthma only. ACO was defined as the presence of all of the following 1) age ≥40 years, 2) current or former smoking, 3) post-bronchodilator airflow limitation (forced expiratory volume in 1 second/forced vital capacity <0.7), and 4) ≥12% and ≥200 ml reversibility in post-bronchodilator forced expiratory volume in 1 second.Results: Among 2,165 individuals (1,015 COPD only, 395 with both asthma and COPD, and 755 asthma only), the overall prevalence of ACO was 20% (95% confidence interval, 18-23%). Patients with ACO had a mean age of 70 years (standard deviation, 11 yr), 60% were men, 73% were former smokers (the rest were current smokers), and 66% were overweight or obese. Comorbid conditions were common in patients with ACO, including diabetes (53%), cardiovascular disease (36%), hypertension (30%), eczema (23%), and rhinitis (21%). The prevalence of ACO was higher in patients with a diagnosis of both asthma and COPD (32%) compared with a diagnosis of COPD only (20%; P < 0.001) or asthma only (14%; P < 0.001). Demographic and clinical characteristics of ACO varied across these three source populations.Conclusions: One in five individuals with a diagnosis of COPD, asthma, or both asthma and COPD in primary care settings have ACO based on the Respiratory Effectiveness Group ACO Working group criteria. The prevalence and characteristics of patients with ACO varies across the three source populations.